The Challenge of Achieving Zero Trust Remote Access in Multi-Cloud Environment - Chimakurthi, Venkata Naga Satya Surendra (ABC Journal of Advanced Research, 2020)
Zero-trust security models and architectures have recently increased in adoption due to several variables, such as the widespread use of off-premises cloud technologies, variety in IT devices, and diffusion in the Internet of Things (IoT). Users, devices, apps, and networks are all assumed to be untrustworthy in this approach, which is built on the idea of various tiers of Trust and authentication. Cybersecurity paradigms are developing, and the term "zero trust" describes the shift from static network perimeters to protecting people, things, and resources. Economic and enterprise architecture and processes can be designed using zero trust principles. In the idea of zero Trust, assets or user accounts are thought to have no implicit confidence because of their physical or network location (Internet vs local networks) or asset ownership (enterprise or personally owned). Authentication and authorization must be conducted before a connection to an organizational resource can be established. There are many different types of Cloud, including several public, private, hybrid, and on-premises. For data centers, a multi-cloud deployment strategy includes many different public cloud service providers instead of relying on a private cloud or on-premises architecture. Hybrid multi-cloud is a multi-cloud implementation that incorporates all public and private clouds and on-premises technology. This paper discusses the zero-trust security model for multi-cloud environments and applications and the obstacles to implementing it.